Molecular cloning of a cell wall exo-beta-1,3-glucanase from Saccharomyces cerevisiae. - Klebl, F (1989)
A major protein of Saccharomyces cerevisiae cell walls is a 29-kilodalton glycoprotein which shows lectinlike binding to beta-1,3-glucan and chitin. It was solubilized by heating isolated cell walls at 90 degrees C and purified to homogeneity by running two high-pressure liquid chromatography columns. With the sequence information of the N terminus and seven peptides, two oligonucleotides were synthesized and the gene was cloned. Its sequence is similar to those of two plant beta-glucanases, and the protein was shown to possess beta-1,3-exoglucanase activity with laminarin as substrate. Haploid yeast cells contained one copy of the gene (BGL2). Gene disruption did not result in a phenotype.